Adsorption of Nonylphenol Polyethoxylate Using HCl-Treated Fish Scales of Barbonymus gonionotus in the Presence of Anionic Surfactant - Thongkon, Nisakorn; Yaodusit , Sureewan; Thongdee, Janjira (Agriculture and Natural Resources, 2015)
The adsorption of nonylphenol polyethoxylate (NPnEO; n=3–13, n 9), by HCl-treated fish scales (HTS) was enhanced significantly after the pre-adsorption of sodium dodecylbenzene sulfonate (SDBS) onto the HTS. The amount of SDBS adsorbed increased with the contact time, resulting in a monolayer coverage of the HTS (SBHTS) before NP9EO adsorption. The maximum percentage of NP9EO adsorption onto the SBHTS was 92.3% for 180 min. The adsorption processes were found to follow a pseudo-second-order type. The adsorption isotherm of NP9EO onto the SBHTS could be explained better using the Langmuir model than with the Freundlich model and the former produced a best fit with a correlation coefficient value of 0.999 and a steric hindrance effect of SDBS. The thermodynamic parameters, the enthalpy, the entropy and the Gibbs free energy changes were calculated as well, and their values indicated that the adsorption processes were spontaneous and endothermic. Investigation of the adsorption ability of fish scales may result in a better understanding of the parent compound (NP9EO) accumulation in fish.